Preparation method of metal ion doped modified manganese-based flexible electrode
Patent Information
- Application Number
- CN202510907573.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-02
- Publication Date
- 2026-10-27
AI Technical Summary
这些方法虽然应用广泛,但普遍存在诸多问题:一方面,制备过程中往往需要高温煅烧,能耗较高,且在高温条件下锰元素容易发生价态变化,导致材料结构不稳定,循环性能和倍率性能下降;另一方面,传统工艺中对材料的微观结构和形貌调控能力有限,难以精准控制颗粒尺寸、形貌及晶面取向等,致使所制材料在电极/电解液界面稳定性、离子扩散速率及电子传输效率等方面表现欠佳
[0023]本发明的有益效果在于:(1)本发明利用聚酰胺酸(PAA)溶液对碳布进行处理以及热处理对碳布改性,改变了碳布的表面性质,增加了表面的活性位点,得到亲水性碳布,从而有利于在电化学沉积法下ε-MnO2、Ca-ε-MnO2、Cu-ε-MnO2和K-ε-MnO2的均匀沉积和附着。通过控制沉积时间能够在室温条件下获得特定结构的二氧化锰并使其负载量均匀,无需高温烧结、高温高压环境等步骤,能够解决现有技术中二氧化锰制备需高能耗的问题;并且,该制备方法无需额外添加强氧化剂,能够减少原料运输、储存以及反应过程中存在的安全隐患,对设备要求较低,利于控制生产成本。
Smart Images

Figure CN122991967A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and specifically to a method for preparing a metal ion-doped modified manganese-based flexible electrode. Background Technology
[0002] Manganese-based cathode materials are a class of lithium-ion battery cathode materials with manganese as the main active material. The multivalent state characteristics of manganese ions in their crystal structure endow the materials with advantages such as high theoretical capacity, moderate voltage platform, abundant resources and low cost. Therefore, they have received widespread attention in the fields of electric vehicles, energy storage systems and portable electronic devices.
[0003] Traditional methods for preparing manganese-based cathode materials mainly include high-temperature solid-state methods, co-precipitation methods, and sol-gel methods. While these methods are widely used, they generally suffer from several problems: Firstly, the preparation process often requires high-temperature calcination, resulting in high energy consumption. Furthermore, manganese is prone to valence state changes at high temperatures, leading to unstable material structures and decreased cycle and rate performance. Secondly, traditional processes have limited ability to control the microstructure and morphology of the materials, making it difficult to precisely control particle size, morphology, and crystal orientation. This results in suboptimal performance in terms of electrode / electrolyte interface stability, ion diffusion rate, and electron transport efficiency. In addition, some methods are complex and inefficient, failing to meet the current requirements for high-performance, low-cost, and green development of lithium-ion battery cathode materials.
[0004] Therefore, this application is submitted. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the existing technology and provide a method for preparing a metal ion-doped modified manganese-based flexible electrode, which can improve the specific capacity, increase the power supply time, and significantly improve the electrochemical performance. It has more stable discharge performance during the electrochemical reaction process and can store more electrical energy.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a metal ion-doped modified manganese-based flexible electrode includes the following steps: (1) The carbon cloth is soaked in a polyacrylic acid solution to obtain coated carbon cloth; (2) Carbonize the coated carbon cloth to obtain hydrophilic carbon cloth; (3) Hydrophilic carbon cloth was electrochemically deposited in a mixed solution to obtain a metal ion-doped modified manganese-based flexible electrode; The mixed solution includes manganese salt and metal salt, wherein the metal salt includes at least one of calcium salt, copper salt, and potassium salt.
[0007] In a preferred embodiment of the present invention, the polyacrylic acid solution comprises polyacrylic acid and a solvent, wherein the solvent comprises N,N-dimethylformamide.
[0008] In a preferred embodiment of the present invention, the polyacrylic acid solution contains 5-20% polyacrylic acid by mass.
[0009] In a preferred embodiment of the present invention, the soaking time is 4 to 12 hours.
[0010] In a preferred embodiment of the present invention, the carbonization temperature is 550~650℃ and the time is 1~4h.
[0011] In a preferred embodiment of the present invention, the manganese salt includes manganese chloride, the calcium salt includes calcium chloride, the copper salt includes copper chloride, and the potassium salt includes potassium chloride.
[0012] In a preferred embodiment of the present invention, the molar ratio of manganese salt to metal salt in the mixed solution is (1~20):1.
[0013] In a preferred embodiment of the present invention, the molar ratio of manganese salt to metal salt in the mixed solution is (1~2):1.
[0014] In a preferred embodiment of the present invention, the concentration of the metal salt in the mixed solution is 0.05~0.06 mol / L.
[0015] In a preferred embodiment of the present invention, during electrochemical deposition, hydrophilic carbon cloth is used as the cathode, a carbon rod is used as the anode, and a saturated calomel electrode is used as the reference electrode.
[0016] In a preferred embodiment of the present invention, the voltage of the electrochemical deposition is 1~1.5V and the time is 400~600s.
[0017] As a preferred embodiment of the present invention, the carbon cloth is further subjected to ultrasonic cleaning and drying before step (1).
[0018] The ultrasonic cleaning process involves sequentially adding 60 mL of ethanol and 60 mL of deionized water to a 100 mL beaker and cleaning the carbon cloth for 10 minutes.
[0019] The carbon cloth is dried at a constant temperature of 70~90℃ for 1~4 hours.
[0020] In a preferred embodiment of the present invention, the electrochemical deposition is performed using a CHI 660E electrochemical workstation with the Amperometric it Curve module selected.
[0021] As a preferred embodiment of the present invention, after electrochemical deposition, the process further includes cleaning and drying.
[0022] In a preferred embodiment of the present invention, the cleaning is performed by washing with ultrapure water 2 to 4 times, and the drying is performed in a vacuum drying oven at 70 to 90°C for 8 to 20 hours.
[0023] The beneficial effects of the present invention are as follows: (1) The present invention uses polyamic acid (PAA) solution to treat carbon cloth and heat treatment to modify carbon cloth, thereby changing the surface properties of carbon cloth, increasing the active sites on the surface, and obtaining hydrophilic carbon cloth, which is conducive to the uniform deposition and adhesion of ε-MnO2, Ca-ε-MnO2, Cu-ε-MnO2 and K-ε-MnO2 under electrochemical deposition. By controlling the deposition time, manganese dioxide with a specific structure can be obtained at room temperature and its loading can be made uniform. There is no need for high temperature sintering, high temperature and high pressure environment and other steps, which can solve the problem of high energy consumption in the preparation of manganese dioxide in the prior art; in addition, the preparation method does not require the addition of strong oxidants, which can reduce the safety hazards in the transportation, storage and reaction of raw materials, and has lower equipment requirements, which is conducive to controlling production costs.
[0024] (2) This invention prepares a product with a specific ratio of Ca by electrochemical deposition. 2+ Cu 2+ K + The doped nano-ε-MnO2 cathode material possesses interlayer metal ions that stabilize its layered structure and promote the increase of oxygen vacancies in manganese dioxide, thereby improving its conductivity and capacity. Furthermore, this nanostructure exhibits high specific surface area and porosity, facilitating sufficient contact between manganese dioxide and the electrolyte. Zinc-ion batteries containing this manganese dioxide cathode material demonstrate high specific capacity and rate performance. Electrochemical tests have proven that its application in secondary batteries exhibits excellent cycle stability and rate performance. Simultaneously, it broadens the scope of application of metal-doped manganese-based cathode materials in the preparation and application of electrode materials for secondary batteries. Attached Figure Description
[0025] Figure 1 SEM images of the electrodes prepared in Example 1 and Comparative Examples 1-3.
[0026] Figure 2 The above are the EDS spectra of the electrodes prepared in Examples 1, 5, 10 and Comparative Example 3.
[0027] Figure 3 The images show the XRD patterns of the electrodes prepared in Examples 1, 5, 10, and Comparative Example 3.
[0028] Figure 4The GCD diagrams of the electrodes prepared in Examples 1, 5, 10, and Comparative Example 3 at a current density of 0.2 A / g are shown.
[0029] Figure 5 The GCD diagrams of the electrodes prepared in Examples 1, 5, 10, and Comparative Example 3 at a current density of 2 A / g are shown.
[0030] Figure 6 The image shows the CV curve of the electrode prepared in Comparative Example 3 after 100 cycles at a scan rate of 1 mV / s.
[0031] Figure 7 The image shows the CV curve of the electrode prepared in Example 1 after 100 cycles at a scan rate of 1 mV / s. Detailed Implementation
[0032] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0033] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0034] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0035] In this application, there are no particular restrictions on the specific dispersion and mixing methods.
[0036] Unless otherwise specified, all components, raw materials, or instruments used in the embodiments and comparative examples of this invention are commercially available, and the same type of components and raw materials are used in each parallel experiment.
[0037] Example 1 A method for preparing a metal ion-doped modified manganese-based flexible electrode includes the following steps: (1) Cut the carbon cloth into 1.1×1.5cm pieces. 2The rectangular shape was cleaned with ethanol and deionized water for 10 min under ultrasonic treatment, and then dried at 80℃ in an oven for 2 h. (2) Pour 10 g of polyamic acid (PAA) and 90 g of N,N-dimethylformamide (DMF) into a 250 mL beaker at a ratio of 1:9, and stir at 520 rpm for 10 min until homogeneous. Then put the cleaned and dried carbon cloth into the beaker, stir at 220 rpm for 6 h, and after fully coating, remove the carbon cloth and place it in an oven at 80℃ for 12 h to dry, thus obtaining carbon cloth coated with a thin film (i.e., coated carbon cloth). (3) Place the coated carbon cloth neatly into a clean ceramic boat, and then place the ceramic boat horizontally into a high-temperature tube furnace. Set the initial temperature to 40℃, the heating time to 56 min, the heating temperature to 600℃, and the holding time to 2 h for high-temperature carbonization to obtain hydrophilic carbon cloth.
[0038] (4) Hydrophilic carbon cloth was electrochemically deposited in a mixed solution, rinsed three times with ultrapure water, and dried at 80°C for 12 h in a vacuum drying oven to obtain a metal ion-doped modified manganese-based flexible electrode (abbreviated as Ca-ε-MnO2@MCC). 1:1 ).
[0039] The mixed solution includes manganese chloride and calcium chloride.
[0040] The molar ratio of manganese chloride to calcium chloride in the mixed solution is 1:1.
[0041] The concentration of calcium chloride in the mixed solution is 0.05 mol / L.
[0042] During electrochemical deposition, hydrophilic carbon cloth was used as the cathode, a carbon rod as the anode, and a saturated calomel electrode as the reference electrode. The voltage for electrochemical deposition was 1.2V, and the time was 500s.
[0043] Example 2 The difference between Example 2 and Example 1 is that the molar ratio of manganese chloride to calcium chloride is 2:1, while everything else is the same.
[0044] The resulting metal ion-doped modified manganese-based flexible electrode is referred to as Ca-ε-MnO2@MCC. 1:2 .
[0045] Example 3 The difference between Example 3 and Example 1 is that the molar ratio of manganese chloride to calcium chloride is 10:1, while all other aspects are the same.
[0046] The resulting metal ion-doped modified manganese-based flexible electrode is referred to as Ca-ε-MnO2@MCC. 1:10 .
[0047] Example 4 The difference between Example 4 and Example 1 is that the molar ratio of manganese chloride to calcium chloride is 20:1, while all other aspects are the same.
[0048] The resulting metal ion-doped modified manganese-based flexible electrode is referred to as Ca-ε-MnO2@MCC. 1:20 .
[0049] Example 5 A method for preparing a metal ion-doped modified manganese-based flexible electrode includes the following steps: (1) Cut the carbon cloth into 1.1×1.5cm pieces. 2 The rectangular shape was cleaned with ethanol and deionized water for 10 min under ultrasonic treatment, and then dried at 80℃ in an oven for 2 h. (2) Pour 10 g of polyamic acid (PAA) and 90 g of N,N-dimethylformamide (DMF) into a 250 mL beaker at a ratio of 1:9, and stir at 520 rpm for 10 min until homogeneous. Then put the cleaned and dried carbon cloth into the beaker, stir at 220 rpm for 6 h, and after fully coating, remove the carbon cloth and place it in an oven at 80℃ for 12 h to dry, thus obtaining carbon cloth coated with a thin film (i.e., coated carbon cloth). (3) Place the coated carbon cloth neatly into a clean ceramic boat, and then place the ceramic boat horizontally into a high-temperature tube furnace. Set the initial temperature to 40℃, the heating time to 56 min, the heating temperature to 600℃, and the holding time to 2 h for high-temperature carbonization to obtain hydrophilic carbon cloth.
[0050] (4) Hydrophilic carbon cloth was electrochemically deposited in a mixed solution, rinsed three times with ultrapure water, and dried at 80°C for 12 h in a vacuum drying oven to obtain a metal ion-doped modified manganese-based flexible electrode (Cu-ε-MnO2@MCC). 1:1 ).
[0051] The mixed solution includes manganese chloride and copper chloride.
[0052] The molar ratio of manganese chloride to copper chloride in the mixed solution is 1:1.
[0053] The concentration of copper chloride in the mixed solution is 0.06 mol / L.
[0054] During electrochemical deposition, hydrophilic carbon cloth was used as the cathode, a carbon rod as the anode, and a saturated calomel electrode as the reference electrode. The voltage for electrochemical deposition was 1.2V, and the time was 500s.
[0055] Example 6 The difference between Example 6 and Example 1 is that the molar ratio of manganese chloride to copper chloride is 2:1, while all other aspects are the same.
[0056] The resulting metal ion-doped modified manganese-based flexible electrode is referred to as Cu-ε-MnO2@MCC. 1:2 .
[0057] Example 7 The difference between Example 7 and Example 1 is that the molar ratio of manganese chloride to copper chloride is 10:1, while all other aspects are the same.
[0058] The resulting metal ion-doped modified manganese-based flexible electrode is referred to as Cu-ε-MnO2@MCC. 1:10 .
[0059] Example 8 The difference between Example 8 and Example 1 is that the molar ratio of manganese chloride to copper chloride is 20:1, while all other aspects are the same.
[0060] The resulting metal ion-doped modified manganese-based flexible electrode is referred to as Cu-ε-MnO2@MCC. 1:20 .
[0061] Example 9 A method for preparing a metal ion-doped modified manganese-based flexible electrode includes the following steps: (1) Cut the carbon cloth into 1.1×1.5cm pieces. 2 The rectangular shape was cleaned with ethanol and deionized water for 10 min under ultrasonic treatment, and then dried at 80℃ in an oven for 2 h. (2) Pour 10 g of polyamic acid (PAA) and 90 g of N,N-dimethylformamide (DMF) into a 250 mL beaker at a ratio of 1:9, and stir at 520 rpm for 10 min until homogeneous. Then put the cleaned and dried carbon cloth into the beaker, stir at 220 rpm for 6 h, and after fully coating, remove the carbon cloth and place it in an oven at 80℃ for 12 h to dry, thus obtaining carbon cloth coated with a thin film (i.e., coated carbon cloth). (3) Place the coated carbon cloth neatly into a clean ceramic boat, and then place the ceramic boat horizontally into a high-temperature tube furnace. Set the initial temperature to 40℃, the heating time to 56 min, the heating temperature to 600℃, and the holding time to 2 h for high-temperature carbonization to obtain hydrophilic carbon cloth.
[0062] (4) Hydrophilic carbon cloth was electrochemically deposited in a mixed solution, rinsed three times with ultrapure water, and dried at 80°C for 12 h in a vacuum drying oven to obtain a metal ion-doped modified manganese-based flexible electrode (Cu-ε-MnO2@MCC). 1:1 ).
[0063] The mixed solution includes manganese chloride and potassium chloride.
[0064] The molar ratio of manganese chloride to potassium chloride in the mixed solution is 1:1.
[0065] The concentration of potassium chloride in the mixed solution is 0.06 mol / L.
[0066] During electrochemical deposition, hydrophilic carbon cloth was used as the cathode, a carbon rod as the anode, and a saturated calomel electrode as the reference electrode. The voltage for electrochemical deposition was 1.2V, and the time was 500s.
[0067] Example 10 The difference between Example 10 and Example 1 is that the molar ratio of manganese chloride to potassium chloride is 2:1, while all other aspects are the same.
[0068] The resulting metal ion-doped modified manganese-based flexible electrode is abbreviated as k-ε-MnO2@MCC. 1:2 .
[0069] Example 11 The difference between Example 11 and Example 1 is that the molar ratio of manganese chloride to potassium chloride is 10:1, while all other aspects are the same.
[0070] The resulting metal ion-doped modified manganese-based flexible electrode is abbreviated as k-ε-MnO2@MCC. 1:10 .
[0071] Example 12 The difference between Example 12 and Example 1 is that the molar ratio of manganese chloride to potassium chloride is 20:1, while all other aspects are the same.
[0072] The resulting metal ion-doped modified manganese-based flexible electrode is abbreviated as k-ε-MnO2@MCC. 1:20 .
[0073] Comparative Example 1 A method for preparing a metal ion-doped modified manganese-based flexible electrode includes the following steps: (1) Cut the carbon cloth into 1.1×1.5cm pieces. 2 The rectangular shape was cleaned with ethanol and deionized water for 10 min under ultrasonic treatment, and then dried at 80℃ in an oven for 2 h. (2) Electrochemical deposition of carbon cloth in a 1 mol / L MnCl2 solution was carried out under the conditions of 1.2 V and 500 s deposition time. The carbon cloth was rinsed three times with ultrapure water and dried in a vacuum drying oven at 80 °C for 12 h to obtain a manganese-based flexible electrode (abbreviated as ε-MnO2@CC).
[0074] During electrochemical deposition, carbon cloth is used as the cathode, carbon rod as the anode, and saturated calomel electrode as the reference electrode.
[0075] Comparative Example 2 A method for preparing a metal ion-doped modified manganese-based flexible electrode includes the following steps: (1) Cut the carbon cloth into 1.1×1.5cm pieces. 2 The rectangular shape was cleaned with ethanol and deionized water for 10 min under ultrasonic treatment, and then dried at 80℃ in an oven for 2 h. (2) Carbon cloth was electrochemically deposited in a mixed solution, rinsed three times with ultrapure water, and dried at 80°C for 12 h in a vacuum drying oven to obtain a metal ion-doped modified manganese-based flexible electrode (abbreviated as Ca-ε-MnO2@CC).
[0076] The mixed solution includes manganese chloride and calcium chloride.
[0077] The molar ratio of manganese chloride to calcium chloride in the mixed solution is 1:1.
[0078] The concentration of calcium chloride in the mixed solution is 0.05 mol / L.
[0079] During electrochemical deposition, hydrophilic carbon cloth was used as the cathode, a carbon rod as the anode, and a saturated calomel electrode as the reference electrode. The voltage for electrochemical deposition was 1.2V, and the time was 500s.
[0080] Comparative Example 3 A method for preparing a metal ion-doped modified manganese-based flexible electrode includes the following steps: (1) Cut the carbon cloth into 1.1×1.5cm pieces. 2 The rectangular shape was cleaned with ethanol and deionized water for 10 min under ultrasonic treatment, and then dried at 80℃ in an oven for 2 h. (2) Pour 10 g of polyamic acid (PAA) and 90 g of N,N-dimethylformamide (DMF) into a 250 mL beaker at a ratio of 1:9, and stir at 520 rpm for 10 min until homogeneous. Then put the cleaned and dried carbon cloth into the beaker, stir at 220 rpm for 6 h, and after fully coating, remove the carbon cloth and place it in an oven at 80℃ for 12 h to dry, thus obtaining carbon cloth coated with a thin film (i.e., coated carbon cloth). (3) Place the coated carbon cloth neatly into a clean ceramic boat, and then place the ceramic boat horizontally into a high-temperature tube furnace. Set the initial temperature to 40℃, the heating time to 56 min, the heating temperature to 600℃, and the holding time to 2 h for high-temperature carbonization to obtain hydrophilic carbon cloth.
[0081] (4) Hydrophilic carbon cloth was electrochemically deposited in 1 mol / L MnCl2 solution, rinsed 3 times with ultrapure water, and dried in a vacuum drying oven at 80°C for 12 h to obtain a metal ion doped modified manganese-based flexible electrode (abbreviated as ε-MnO2@MCC).
[0082] During electrochemical deposition, hydrophilic carbon cloth was used as the cathode, a carbon rod as the anode, and a saturated calomel electrode as the reference electrode. The voltage for electrochemical deposition was 1.2V, and the time was 500s.
[0083] Test case The assembled aqueous zinc-ion battery was charged and discharged at 25℃ using a small current of 0.2 A / g and a large current of 2 A / g to investigate the electrochemical performance of the material. The test voltage range was 0.5 V–1.5 V, and the test instrument was a CHI 660E electrochemical workstation. The results are shown in Table 1.
[0084] SEM images of the electrode materials prepared in Example 1 and Comparative Examples 1-3 are shown below. Figure 1 As shown, where Figure 1 a is the SEM image of Comparative Example 1. Figure 1 b is the SEM image of Comparative Example 2. Figure 1 c is the SEM image of Comparative Example 3. Figure 1 d is a diagram of Example 1.
[0085] The EDS spectra of the electrode materials prepared in Examples 1, 5, 10, and Comparative Example 3 are as follows: Figure 2 As shown, in Comparative Example 3, ... Figure 2 As shown in Figure a, Example 1 is as follows Figure 2 As shown in b, Example 5 is as follows Figure 2 As shown in d, Example 10 is as follows Figure 2 As shown in d.
[0086] The XRD patterns of the electrode materials prepared in Examples 1, 5, 10, and Comparative Example 3 are shown below. Figure 3 As shown.
[0087] The GCD diagrams of the electrode materials prepared in Examples 1, 5, 10, and Comparative Example 3 at a current density of 0.2 A / g are shown below. Figure 4 As shown.
[0088] The GCD diagrams of the electrode materials prepared in Examples 1, 5, 10, and Comparative Example 3 at a current density of 2 A / g are shown below. Figure 4 As shown.
[0089] The CV curve of the electrode material prepared in Comparative Example 3 after 100 cycles at a scan rate of 1 mV / s is shown in the figure. Figure 6 As shown.
[0090] The CV curve of the electrode material prepared in Example 1 after 100 cycles at a scan rate of 1 mV / s is shown below. Figure 7 As shown.
[0091] Table 1 from Figures 1-7 As can be seen from Table 1, the main structure of the carbon cloth was not destroyed during the modification process of this invention, and ε-MnO2 was successfully deposited on CC and MCC. 2+ Cu 2+ K + After doping, the pore size of the carbon cloth was significantly increased, exhibiting an open nanowire structure. 2+ Successfully doped into ε-MnO2, and uniformly deposited on the carbon cloth surface along with the ε-MnO2. Appropriate Ca... 2 + Cu 2+ K + Doping enhances the conductivity of materials and has a significant synergistic effect with ε-MnO2, widening the lattice spacing and facilitating ion transport. This results in higher specific capacity, longer power supply time, significantly improved electrochemical performance, more stable discharge performance during electrochemical reactions, and the ability to store more electrical energy. In summary, the technical solution of this invention possesses superior specific capacity and excellent cycle stability.
[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a metal ion-doped modified manganese-based flexible electrode, characterized in that, Includes the following steps: (1) The carbon cloth is soaked in a polyacrylic acid solution to obtain coated carbon cloth; (2) Carbonize the coated carbon cloth to obtain hydrophilic carbon cloth; (3) Hydrophilic carbon cloth was electrochemically deposited in a mixed solution to obtain a metal ion-doped modified manganese-based flexible electrode; The mixed solution includes manganese salt and metal salt, wherein the metal salt includes at least one of calcium salt, copper salt, and potassium salt.
2. The method for preparing the metal ion-doped modified manganese-based flexible electrode according to claim 1, characterized in that, The polyacrylic acid solution comprises polyacrylic acid and a solvent, wherein the solvent comprises N,N-dimethylformamide.
3. The method for preparing the metal ion-doped modified manganese-based flexible electrode according to claim 1, characterized in that, The polyacrylic acid solution contains 5-20% polyacrylic acid by mass.
4. The method for preparing the metal ion-doped modified manganese-based flexible electrode according to claim 1, characterized in that, The soaking time is 4 to 12 hours.
5. The method for preparing the metal ion-doped modified manganese-based flexible electrode according to claim 1, characterized in that, The carbonization temperature is 550~650℃, and the time is 1~4h.
6. The method for preparing the metal ion-doped modified manganese-based flexible electrode according to claim 1, characterized in that, The manganese salt includes manganese chloride, the calcium salt includes calcium chloride, the copper salt includes copper chloride, and the potassium salt includes potassium chloride.
7. The method for preparing the metal ion-doped modified manganese-based flexible electrode according to claim 1, characterized in that, The molar ratio of manganese salt to metal salt in the mixed solution is (1~20):
1.
8. The method for preparing the metal ion-doped modified manganese-based flexible electrode according to claim 1, characterized in that, The concentration of the metal salt in the mixed solution is 0.05~0.06 mol / L.
9. The method for preparing the metal ion-doped modified manganese-based flexible electrode according to claim 1, characterized in that, During electrochemical deposition, hydrophilic carbon cloth is used as the cathode, carbon rod as the anode, and saturated calomel electrode as the reference electrode.
10. The method for preparing the metal ion-doped modified manganese-based flexible electrode according to claim 1, characterized in that, The electrochemical deposition voltage is 1~1.5V, and the time is 400~600s.